A rasura oral nos processos de escritura em ato: descrição em poemas escritos por alunos do 3º ano do ensino fundamental - Santos, Cyntya Mayryele Assis dos (2014)
This study describes the occurrence of "oral erasures" presented in dialogic texts in two processes of writing as an act of poems created by pairs of students of a 3rd year of elementary school to a charity school located on the outskirts of Maceió. The oral erasure is a co-enunciatio phenomenon, and it arises when two students write a single one poem in the classroom, from a teacher / coordinator request. Being the oral singular erasures both for speech, as for writing, the filmings are the main object of our work, because they preserve the classroom characteristics and the directions given by the teacher / coordinator. The oral erasures detected in students' speech mark the tension of the process of writing of a school manuscript; manuscript under-stood as anything that has been written by hand and it was not published yet. The challenge is to identify what each erasure oral brings us: the non-coincidence of speech, the pragmatic glosses, lexical, orthographic-graphic, textual. The creativity and the discussions of each pair had given to us the opportuni-ty to observe the leading of this process of writing by two. For this work we base it in the theoretical framework for studious of Genetic Criticism, as Biasi, in Authier-Revuz’s readings, about the non- coincidence of speech, in the Calil’s studies about the oral erasure and the writing process by two. For the methodology the usage of the computer program ELAN, assisted us in the transcriptions and descriptions of the erasures effected by the dyad on this process.